Anti-peripheral myelin antibody in patients with demyelinating neuropathy: quantitative and kinetic determination of serum antibody by complement component 1 fixation. - Koski, C L (1985)
The role of anti-peripheral nerve myelin antibody (anti-PNM Ab) in the pathogenesis of acquired demyelination of peripheral nerve is unclear, in part, due to the poor correlation between antibody and disease activity. Previous studies show that only 27-50% of patients with acute demyelinating neuropathy or Guillain-Barré syndrome (GBS) had serum Abs to peripheral nerve or PNM as demonstrated by consumption of hemolytic activity of serum complement 1 (C1) fixation and transfer assay, quantitative determinations of anti-PNM Ab showed significantly high titers in the serum of patients with GBS, chronic and recurrent polyneuritis, and paraproteinemia associated with peripheral neuropathy. All 11 patients with acute-phase GBS had Ab titers 6-56 times higher than controls. In 6 GBS patients, serial Ab determinations showed that titers were highest on admission, fell rapidly the first week, and became undetectable or barely detectable by the third week. Declining Ab titers coincided with cessation of clinical progression. In 3 GBS patients, depletion of serum IgM lowered anti-PNM Ab titers significantly, whereas IgG depletion failed to produce a similar effect. This study shows that the C1 fixation and transfer assay is a sensitive method to detect anti-PNM Ab in the serum of patients with a variety of demyelinating neuropathies and provides good correlation between Ab level and the clinical course of GBS patients. It may provide important information about the pathogenesis of the demyelinating neuropathies.